Craft villages and tourism development, a case study in Phu Quoc island of Vietnam - Hieu Vu Minh; Rasovska Ida (Management)
Craft tourism is attracting many domestic and foreign tourists. In recent years in Vietnam, craft villages have exploited their potentials in tourism industry. For many different causes, tourism activities have yet reached expectations and their potentials for tourism development. This paper is to review their currents, tourism potentials and limitations and then formulate recommendations to the tourism development in Phu Quoc island. The data for this paper are from two sources. Secondary data were collected from the vast literature and journals. Primary data were from interviews with village owners, related authorities, tourists, tourism corporate, etc. and results serve as guidelines to develop the tourism industry and management.